Business Incubators in Russia: 2020 Survey in International Comparative Perspective - M. A. Slesarev (Vestnik MGIMO-Universiteta, 2022)
Small innovative and venture enterprises face significant financial and managerial difficulties in the early stages of their development, which makes it necessary to provide them with sufficient support at the start. Different governments choose different ways to solve this problem. In Russia, in the 2010s, an emphasis was made on creating business incubators as SME support infrastructure and key players (as well as a potential driver) of regional entrepreneurial ecosystems. Nevertheless, the latest official data shows that the number of business incubators in Russia has gradually declined over the past five years, making it a critical phenomenon to analyze. We conducted a comprehensive survey among a selection of Russian business incubators.Comparing the world BI average characteristics (secondary data from InBIA, International Business Innovation Association) and UBI Global (the data obtained through Surveys conducted in 2012, 2016, and 2020) helps us understand the actual state and dynamics of business incubation in Russia. The surveys contain a wide range of questions covering essential aspects of business incubators' activities, including BI program, clients, environment, effectiveness, and finance.The study shows that business incubators in Russia have undergone several external positive changes, including increased square space, staff quantity, the average annual number of residents, the annual budget, etc. At the same time, the total number of business incubators also significantly dropped, which means that all of the above positive changes do not reflect the growth of the business incubation market and the scaling of the most effective structures; on the contrary, it is an optimization.As a result of the study, we formulate several additional questions for future research and study to understand better the challenges business incubators currently face in Russia, the reasons for their recent consolidation, and possible ways out.